Encapsulation of Phloroglucinol from Rosenvingea intricata Macroalgae with Zinc Oxide Nanoparticles against A549 Lung Cancer Cells - Sakthivel Muthu; Mythileeswari Lakshmikanthan; Edwin Edward-Sam; Mutheeswaran Subramanian; Lakshmanan Govindan; Afrina Begum Mithen Patcha; Kathiravan Krishnan; Nallusamy Duraisamy; Selvakumari Jeyaperumal; Al Thabiani Aziz (MDPI AG, 2024)
Background/Objectives: Phloroglucinol (PHL), a phenolic compound extracted from the brown alga Rosenvingea intricata, exhibits potent antioxidant and anticancer properties. This study aims to extract, purify, and characterize PHL, and further develop functionalized zinc oxide nanoparticles (ZnO NPs) loaded with PHL to enhance its therapeutic potential. Methods: PHL was extracted using acetone and purified through Sephadex LH-20 column chromatography, yielding a highly enriched fraction (F-3). The purified compound was characterized by FTIR, HPLC, NMR, and LC-MS. ZnO NPs were synthesized, PEGylated, and conjugated with PHL, forming ZnO-PEG-PHL NPs. Their characterization included DLS, zeta potential, XRD, SEM-EDAX, and encapsulation efficiency studies. Antioxidant assays (DPPH, FRAP, ABTS, RPA) were performed and in vitro cytotoxicity on A549 lung cancer cells were determined to evaluate the therapeutic efficacy of PHL. Results: The purified PHL fraction showed a high phenolic content (45.65 PHL mg/g), which was was confirmed by spectral analysis. The ZnO-PEG-PHL NPs increased in size from 32.36 nm to 46.68 nm, with their zeta potential shifting from −37.87 mV to −26.82 mV. The antioxidant activity was superior for the ZnO-PEG-PHL NPs in all assays, while the in vitro cytotoxicity tests showed an IC50 of 40 µg/mL compared to 60 µg/mL for the ZnO NPs and 70 µg/mL for PHL. Apoptotic studies revealed significant cell cycle arrest and apoptosis induction. Conclusions: The synthesized ZnO-PEG-PHL NPs demonstrated enhanced antioxidant and anticancer properties, making them promising candidates for cancer therapy and antioxidant applications.